2012
DOI: 10.1208/s12249-012-9862-8
|View full text |Cite
|
Sign up to set email alerts
|

The Improvement of the Anticancer Effect of a Novel Compound Benzoic Acid, 2-Hydroxy-, 2-d-ribofuranosylhydrazide (BHR) Loaded in Solid Lipid Nanoparticles

Abstract: Abstract. A novel drug delivery system consisting of benzoic acid, 2-hydroxy-, 2-D-ribofuranosylhydrazide (BHR)-loaded solid lipid nanoparticles (BHR-SLNs) was prepared using the emulsification-evaporation technique. The mean particle size of the BHR-SLNs measured by photon correlation spectroscopy was about 75 nm. BHR-SLN morphology was assessed by transmission electron microscopy and atomic force microscopy. The drug entrapment efficiency was 70.2%, as determined via Sephadex gel chromatography and high-perf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…Among the above, SLNs may be an alternative drug carrier system that offers several advantages conferred by their colloidal dimensions, including: easy incorporation of both lipophilic and hydrophilic drugs; improved biocompatibility; flexible surface functionality; nanoscopic structure; monodispersity; and high encapsulation efficiency (Muller and Keck 2010; Alpiaz et al 2008; Carneiro et al 2012; Jaspart et al 2005; Shuhendler et al 2012; Wang et al 2012; Yang et al 2012). …”
Section: Introductionmentioning
confidence: 99%
“…Among the above, SLNs may be an alternative drug carrier system that offers several advantages conferred by their colloidal dimensions, including: easy incorporation of both lipophilic and hydrophilic drugs; improved biocompatibility; flexible surface functionality; nanoscopic structure; monodispersity; and high encapsulation efficiency (Muller and Keck 2010; Alpiaz et al 2008; Carneiro et al 2012; Jaspart et al 2005; Shuhendler et al 2012; Wang et al 2012; Yang et al 2012). …”
Section: Introductionmentioning
confidence: 99%
“…The treatment of 293T and Hela cells with BHR-SLNs demonstrated that BHR-SLNs were less toxic than normal cells, while more effective in antitumor potency compared with the BHR drug alone. These results showed that BHR-SLNs could be considered as a promising antitumor drug system for a range of new therapeutic applications (Wang et al, 2012b). as surfactant.…”
Section: In Vitro Studiesmentioning
confidence: 88%
“…36 The zeta potential of NCNLCs was distributed between −3.5 mV and −5.2 mV, a lightly negative charge, suggesting good stability and high cellular uptake, and also facilitating the delivery of NCNLCs to the negatively charged cancer cells. 37 The DEE and DLC of NG encapsulated in NCNLCs were 91.77±0.48%, and 6.96±0.02%, separately ( Figure 2C). In order to investigate the influence of CSO as liquid lipids, the morphology of NCNLCs was also determined in Figure 2A and B, displayed as spherical particles with around 50 nm, which was essentially in agreement with the results of photon correlation spectroscopy analysis.…”
Section: Preparation and Characterization Of Ncnlcsmentioning
confidence: 94%